The role of nitric oxide synthase and cystatin C in the mechanisms of antimicrobial protection in children with urinary tract infections considering the etiological factor - Lezhenko, H. O.; Zakharchenko, N. A. (Zaporozhye Medical Journal, 2022)
The aim of the study was to investigate the main etiological factors of urinary tract infections in children, the role of nitric oxide synthase and cystatin C in the mechanisms of antimicrobial protection in children with acute and chronic urinary tract infections. Materials and methods. The study groups consisted of 84 children (mean age – 10.0 ± 1.3 years). The main group was divided into subgroups: the first subgroup – 17 children with acute pyelonephritis, the second subgroup – 21 patients with chronic pyelonephritis, the third subgroup – 16 patients with acute cystitis, the fourth subgroup – 10 patients with unspecified urinary tract infections. The control group consisted of 20 relatively healthy children. The levels of inducible NO-synthase (NOS2) and cystatin C were measured by enzyme-linked immunosorbent assay. The etiological pathogen was identified in the urine of 200 patients with urinary tract infections. Results. Escherichia coli was identified as the dominant pathogen in 46.7 % of cystitis patients and in 66.6 % of chronic pyelonephritis patients. The next most frequently detected etiological agent in children with acute (27.3 % of cases) and chronic (25.6 %) pyelonephritis and unspecified urinary tract infection (32.2 %) was Enterococcus faecium. Proteus mirabilis was found in 26.6 % of patients with cystitis. The level of NOS2 in all the studied subgroups was significantly higher than that in the control group (P < 0.01). A statistically significant increase in the level of cystatin C in the main group (P < 0.05) was determined. The cystatin C-to-NOS2 ratios in the studied subgroups were 1.5–2.0 times lower than those in the control group (P < 0.05). Conclusions. The change in the spectrum of pathogens has been determined, which was a premise of the need for constant bacteriological monitoring. The development of the primary inflammatory process in the urinary tract occurred amidst a certain dysfunction of the immune system, which was manifested in an insufficient quantitative response of cystatin C, as well as high serum levels of inducible NO-synthase in the patients.